The influence of personality disorder indication, social support, and grief on alcohol and cocaine use among HIV-positive adults coping with AIDS-related bereavement. - Hansen, Nathan B; Cavanaugh, Courtenay E; Vaughan, Ellen L; Connell, Christian M; Tate, David C; Sikkema, Kathleen J (AIDS and behavior, 2009)
Substance use is prevalent among HIV-positive adults and linked to a number of adverse health consequences; however little is known about risk and protective factors that influence substance use among HIV-positive adults coping with AIDS-related bereavement. Using structural equation modeling (SEM), male gender, diagnostic indications of antisocial and borderline personality disorders (PD), and grief severity were tested as risk factors, and social support as a protective factor, for alcohol and cocaine use among a diverse sample of 268 HIV-positive adults enrolled in an intervention for AIDS-related bereavement. Results indicated that the hypothesized model fit the study data. Male gender, PD indication, and social support had direct effects on substance use. PD had significant indirect effects on both alcohol and cocaine use, mediated by social support, but not by grief. Finally, both PD and social support had significant, but opposite, effects on grief. Implications for intervention and prevention efforts are discussed.
Keywords: Acquired Immunodeficiency Syndrome; Adaptation, Psychological; Adult; Alcohol Drinking; Bereavement; Cocaine-Related Disorders; Depression; Female; Grief; HIV Infections; Humans; Male; Personality Disorders; Social Support; Stress, Psychological